2022
DOI: 10.1007/s11012-022-01525-5
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigations of the vortex feature-based vorticity confinement models for the assessment in three-dimensional vortex-dominated flows

Abstract: In order to improve the vortex resolution in aerodynamic wakes, a locally normalized vortex feature-based vorticity confinement method is implemented into the multi-block, structured computational fluid dynamics solver (ROSITA). In this method, the second vorticity confinement (VC2) scheme with two well-known vortex feature detection methods (non-dimensional Q criterion, non-dimensional $$\lambda _2$$ λ 2 criterion) is employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In this work, the VC2 scheme, which has better numerical properties in conservation and regularity at the vortex center, is used to preserve vorticity in helicopter rotor flows. The implementation of the VC2 scheme relies on the experience of our past studies [8,11], that is, considering the vorticity confinement term as a body force source term f b on the momentum equation alone. This approach is preferred since the treatment that removes the vorticity confinement term from the energy conservation equation could obtain far better results [18].…”
Section: Vortex Feature-based Vorticity Confinement Schemementioning
confidence: 99%
See 4 more Smart Citations
“…In this work, the VC2 scheme, which has better numerical properties in conservation and regularity at the vortex center, is used to preserve vorticity in helicopter rotor flows. The implementation of the VC2 scheme relies on the experience of our past studies [8,11], that is, considering the vorticity confinement term as a body force source term f b on the momentum equation alone. This approach is preferred since the treatment that removes the vorticity confinement term from the energy conservation equation could obtain far better results [18].…”
Section: Vortex Feature-based Vorticity Confinement Schemementioning
confidence: 99%
“…The FVC2-Q and FVC2-L2 schemes have been used in 3D flows that are dominated by vortices. Recent studies have shown that the FVC2-L2 scheme performs better than the FVC2-Q scheme in terms of computational stability, aerodynamic prediction, and vorticity preservation [11]. Based on this finding, the threshold function of the non-dimensional λ 2 criterion can be expressed as follows:…”
Section: Vortex Feature-based Vorticity Confinement Schemementioning
confidence: 99%
See 3 more Smart Citations